Rare causes of acute coronary syndrome: in addition to coronary artery atherosclerosis - Beglan Stambol; Dametay Baizhumanova; Aliya Mukazhanova; Gulzi Kussaiynkhan; Darkhan Teleubayev (National Scientific Medical Center, 2016)
In this letter we discussed the rare cause of acute coronary syndrome, such as blockage of a coronary artery, coronary artery tear (dissection), aortic rupture, hyperthyroidism, carbon dioxide poisoning, congenital coronary artery disease Tako-Tsubo heart muscle.